Prehistory : A Very Short Introduction - Gosden, Chris 1955- (Karachi Oxford University Press, 2009)
From the Publisher: Many of the familiar aspects of modern life are no more than a century or two old, yet our deep social structures and skills were in large measure developed by small bands of our prehistoric ancestors many millennia ago. In this book, readers are invited to think seriously about who we are by considering who we have been.
Include Maps, Pictures and Index
Keywords: Civilization, Ancient -- History, Ancient